UPDATE MANAGEMENT CONCURRENT INFECTION BETWEEN DENGUE VIRAL AND SALMONELLA - Wikanesthi, Dyah; Sari, Desiana W; Chilvia, Eva; Soedirham, Oedojo; Kurniasari, Lely; Soegijanto, Soegeng (Institute of Topical Disease, 2014)
Since Januari 2013, Soerya Hospital has found many cases with positive result of IgM Salmonella along with NS1 or IgM &Â IgG Dengue. The clinical manifestations mostly are high fever, headache, vomiting, malaise and plasma leakage. Some of them withÂ convulsion and unconsciousness. Therefore in order to get well of care management, this clinical phenomena should be studied carefully.Â The aim of this research is to get update management concurent Dengue Viral and Salmonella infection. Observational study had beenÂ done, since Januari 2013 until Juli 2013. Purposive sampling in 30 case of concurent Dengue Viral and Salmonella infection comparedÂ with 30 case of Dengue Viral infection alone. Diagnosis has published based on WHO 2011 criteria. By using anti vomiting drug, antiÂ pyretic, anti convulsion and antibiotic for Salmonella infection and rehidration using Ringer Acetate, combining Ringer Asetat andDextrose 5% or combining Ringer Asetat Saline 0,225% or solution of Dextrose 5% and Saline 0,45 during 4â5 days hospitalization.Â The result show that all cases were recovered and got well. There is no significant different between concurent Dengue Viral andÂ Salmonella infection compared with Dengue Viral infection alone. Some cases showed that length time to stay in hospital become1â2 days longer. It was due to delayed getting antibiotic for Salmonella infection. All cases had got first drugs accurately in a clinicalÂ manifestation that has been daily showed. It was as a problem solving for saving all the cases.